Development of a nano-satellite - Tan, Chun Kiat. (2011)
Pico/nano-satellite refers to a class of satellite that weigh less than 10kg. Lightweight lowers the cost to develop, test and launch. Standardization defined by CalPoly, known as the CubeSat specifications further simplified the development process of pico/ nano-satellite. The VELOX-I is the pioneer satellite under the Undergraduate Satellite Program in Nanyang Technological University (NTU). This report focuses on the structure subsystem of VELOX-I which consists of P-Sat and N-Sat. The structure subsystem includes a primary outer structure and a secondary structure. The primary structure shields the satellite system bus from environmental impact while the secondary structure houses the satellite system bus. Mechanisms such as the optics deployment, solar panel deployment and inter-satellite separation mechanisms were also developed. Finite element analysis was carried out to evaluate the structural strength before the environmental and functional tests were conducted. The environmental and functional tests provided a physical means to qualify the structure and its mechanisms. Results from the tests benchmarked the ability of VELOX-I structure subsystem to survive the launch and to fulfil the mission requirements.